Robot Light Skin' paper data for Figures 5-11 - chun gilbert Tang, Chi; Webb, Phil; Thrower, John (Cranfield University, 2018)
Experiment data used in the publication "The development and evaluation of Robot Light Skin: A novel robot signalling system to improve communication in industrial human–robot collaboration" for the concept validation of the Robot Light Skin (RLS), the data included correspond to the following figures in the publication: Reaction time to light signals fig 5, hit-rate fig 6, task performance fig 7, ease of monitoring fig 8, level of tiredness fig 9, and eye tracking fixation time fig 10 and 11.
Keywords: Human Robot Interaction'; 'Interactive Tool'; 'robotics technologies'; 'Manufacturing Robotics and Mechatronics (excl. Automotive Mechatronics)'